A critical review of social media research in sensory-consumer science. (March 2023) - Hutchings, Scott C.; Dixit, Yash; Al-Sarayreh, Mahmoud; Torrico, Damir D.; Realini, Carolina E.; Jaeger, Sara R.; Reis, Marlon M.
Graphical abstract: Highlights: Sensory-consumer research using social media has grown rapidly from 2013 to 2022. This review investigated the pros and cons of social media v conventional methods. Findings showed conventional methods have more control over participant biases. Conventional methods offered superior discrimination for food product research. Social media methods offered benefits for studying trends and cross-cultural insights. Abstract: The collection and analysis of digital data from social media is a rapidly growing methodology in sensory-consumer science, with a wide range of applications for research studying consumer attitudes, preferences, and sensory responses to food. The aim of this review article was to critically evaluate the potential of social media research in sensory-consumer science with a focus on advantages and disadvantages. This review began with an exploration into different sources of social media data and the process by which data from social media is collected, cleaned, and analyzed through natural language processing for sensory-consumer research. It then investigated in detail the differences between social media-based and conventional methodologies, in terms of context, sources of bias, the size of data sets, measurement differences, and ethics. Findings showed participant biases are more difficult to control using social media approaches, and precision is inferior to conventional methods. However, findings also showed social media methodologies may have other advantages including an increased ability to investigate trends over time and easier access to cross-cultural or global insights. Greater research in this space will identify when social media can best function as an alternative to conventional methods, and/or provide valuable complementary information.